A Novel Visually Guided Radiofrequency Balloon Ablation Catheter for Pulmonary Vein Isolation: One-Year Outcomes of the Multicenter AF-FICIENT I Trial. (29th September 2021) - Reddy, Vivek Y.; Al-Ahmad, Amin; Aidietis, Audrius; Daly, Matthew; Melton, Iain; Hu, Yan; Sulkin, Matthew; Rackauskas, Gediminas; Ebner, Adrian; Hooks, Darren A.; Sofi, Aamir; Neužil, Petr; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: A multielectrode saline-irrigated radiofrequency (RF) balloon catheter with an integrated camera system was designed to perform single-shot pulmonary vein (PV) isolation. To optimize ablation, simultaneous circumferential RF energy can be delivered, albeit with power output that is tailored to individual electrodes based on direct visualization of tissue-electrode contact. In a first-in-human multicenter clinical trial, we studied the feasibility, performance, safety, and efficacy of PV isolation using this novel ablation catheter to treat atrial fibrillation. Methods: AF-FICIENT-I was a prospective, 5-center, single-arm study. After transseptal puncture, the RF balloon was positioned over the wire at each pulmonary (PV) ostium using a 13.3F sheath. RF energy was titrated based on visual contact (6–10 W; up to 60 seconds per ablation). Electrical PV isolation was confirmed using either, (1) sensing mini-electrodes situated on the RF balloon itself or (2) a circular mapping catheter. Patients were clinically assessed for recurrent atrial arrhythmias lasting >30 s over 12 months, after a 3-month blanking period. Results: Six operators performed de novo PV isolation in 99 patients (95 paroxysmal/4 persistent; age, 58±11; men, 67.7%). Median times, including procedure, fluoroscopy, ablation (time from first RF to last RF application), and balloon (time elapsing between catheter introduction to removal from the body) times, were 85 (interquartile range, 62–118), 14 (interquartile range, 9–23), 31 (interquartile range, 20–53), and 43 minutes (interquartile range, 32–70), respectively. The 12-month Kaplan-Meier estimates of freedom from any atrial arrhythmia (atrial fibrillation, atrial flutter, or atrial tachycardia) or atrial fibrillation alone were 77.5% (95% CI, 67.6%–84.7%) and 84.1% (95% CI, 74.9%–90.1%), respectively. There were no device-related serious adverse events. Conclusions: The novel RF balloon catheter allowed visually guided, directional titration of ablative energy to safely isolate PVs with short procedure times. Registration: URL: https://www.anzctr.org.au ; Unique identifier: ACTRN12615001340527.